Peran Pola Asuh Orang Tua dengan Tingkat Kecemasan Remaja Sekolah Selama Pendidikan Daring di Masa Pandemi Covid-19 - Retno Yuli Hastuti; Sarida; Puput Risti Kusumaningrum (Universitas Muhammadiyah Klaten, 2024)
Positive cases of Covid-19 in Indonesia have jumped rapidly since March, recorded in the hundreds. The high number of Covid-19 cases in Indonesia has prompted the government to issue new policies that must be implemented to reduce the transmission of Covid-19. Implementation of home learning policies (online). ) makes some students anxious and depressed, many assignments given by teachers make many students stressed. This research design uses quantitative research using a descriptive correlation approach. Sampling in this research used a purposive sample with a sample of 131 at SMP N 4 Karanganom. Data collection used a parenting style questionnaire and the HARS questionnaire. The statistical test used is the Kendall Tau test. The research results showed that the most common parenting style that respondents received from their parents was democratic parenting, namely 91 respondents (69.5%) and the highest level of anxiety experienced by respondents was mild anxiety, 94 respondents (70.1%). The Kendall Tau statistical test result is 0.000, which is smaller than the significance level used of 0.05. Thus, it can be concluded that there is a relationship between parental care patterns and the level of anxiety of school teenagers in facing education during the Covid-19 pandemic at SMP N Karanganom. There is a relationship between parenting styles and children's anxiety levels in facing education during the Covid-19 pandemic.